Pediatric Myocarditis: What Have We Learnt So Far? - Elettra Pomiato; Marco Alfonso Perrone; Rosalinda Palmieri; Maria Giulia Gagliardi (Journal of Cardiovascular Development and Disease, 2022)
Myocarditis is an inflammatory disease of the myocardium that is troublesome to diagnose and manage, especially in children. Since the introduction of endomyocardial biopsy (EMB), new diagnostic tools have provided useful data. Especially when enhanced with immunohistochemistry and polymerase chain reaction (PCR) studies, EMB remains the gold standard for the diagnosis. Notably, cardiac magnetic resonance (MRI) is a non-invasive tool that can confirm the diagnosis and has a particular usefulness during the follow-up. The causes of myocarditis are heterogeneous (mostly viral in children). The course and outcome of the illness in the pediatric population represent a complex interaction between etiologic agents and the immune system, which is still not fully understood. The clinical presentation and course of myocarditis vary widely from paucisymptomatic illness to acute heart failure refractory to therapy, arrhythmias, angina-like presentation and sudden cardiac death. In this setting, cardiac biomarkers (i.e., troponins and BNP), although unspecific, can be used to support the diagnosis. Finally, the efficacy of therapeutic strategies is controversial and not confirmed by clinical trials. In this review, we summarized the milestones in diagnosis and provided an overview of the therapeutic options for myocarditis in children.